Diffuse Palmar Hyperpigmentation In Lichen Planus - Vijaikumar M; Thappa D M; Gupta S (Wolters Kluwer Medknow Publications, 2001)
A 62 year old male agricultural labourer presented with itchy pigmented lesions involving mainly upper and lower limbs of 6 months duration. On physical examination he had macular and popular hyperpigmented violaceous lesions associated with Koebner phenomenon. Palms and soles demonstrated diffuse as well as macular type of huperpigmentation. Histopathological examination of forearm lesion showed basal cell liquefactive degeneration with melanin incontinence suggestive of healing lichen planus. The case is reported for the unusual palmoplantar lesion seen in our case.